Failure analysis of a damaged diesel motor crankshaft. (August 2019) - Fonte, M.; Freitas, M.; Reis, L.
Abstract: A case study of a catastrophic failure of a diesel motor crankshaft is presented. The aim of this failure analysis is to investigate the root cause of this important mechanical component. This crankshaft belonged to a particular vehicle (140 cv, at 4000 rpm, 1968 cm3 displacement) that fractured after 180, 000 km and 8 years in service. The motor was disassembled, and the crankpin No. 3 and the main bearing cap No. 4 were broken. Defects of material and machining defects were not found at the crack initiation sites by optical and SEM microscope. Results shown that the crankpin and the main bearing cap clearly failed by fatigue, and the root cause seems to be related with deficient tightening of the main bearing cap No. 4, which fractured due to a crack developed on the its outer side. The main journal No. 4 did run out of support, and the crankthrow No. 3 increased the alternating stress amplitude, whereby an inevitable catastrophic crankshaft failure happened. Highlights: A detailed failure analysis of a damaged diesel motor crankshaft was performed. The effect of fretting wear on the crack initiation was analysed. The main bearing cap influence on crankshaft failure The importance of bolts pre-tightening Main bearing cap quality control on the fatigue strength of crankshafts